2021
DOI: 10.1177/14777606211038951
|View full text |Cite
|
Sign up to set email alerts
|

Thermal aging behaviors of the waste tire rubber used in bitumen modification

Abstract: Considering the application scenarios of rubber granules from waste tires in the bitumen modification process (wet or dry process), both aerobic and anaerobic aging of rubber may occur. The current study aims to investigate the thermal aging behavior of waste tire rubber samples using nanoindentation and environment scanning electron microscopy (ESEM) tests. Both aerobic and anaerobic aging tests with different durations were conducted on rubber samples. The complex moduli of aged rubber samples were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, the results reveal that combining CLNR with PPA not only improves hightemperature properties but also increases resistance to shearing at high temperatures [20]. This condition is due to the shift of the bitumen structure from sol-type to gel, at which a strong colloidal structure is generated due to the high concentration and volume of resins and asphaltenes, resulting in a change in the bitumen's viscoelastic behaviour, hence enhancing its high-temperature performance [56,58,80]. This result agreed with previous studies that found that adding PPA to CR, SBS/SBR and DRMA can improve the hightemperature performance of the composite bitumen [16,31,59,72].…”
Section: Polyphosphoric Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the results reveal that combining CLNR with PPA not only improves hightemperature properties but also increases resistance to shearing at high temperatures [20]. This condition is due to the shift of the bitumen structure from sol-type to gel, at which a strong colloidal structure is generated due to the high concentration and volume of resins and asphaltenes, resulting in a change in the bitumen's viscoelastic behaviour, hence enhancing its high-temperature performance [56,58,80]. This result agreed with previous studies that found that adding PPA to CR, SBS/SBR and DRMA can improve the hightemperature performance of the composite bitumen [16,31,59,72].…”
Section: Polyphosphoric Acidmentioning
confidence: 99%
“…However, too much sulphur will prevent the desulphurisation and deterioration of the CR in the bitumen, which would harm the CRMA's low-temperature performance. The blending process was performed under a shearing time of 120 min at 180 • C and is similar to that performed by S. Wang, Huang, Liu, Lin et al [58]. In the application of SBS, 1% sulphur was added to 2% of SBS with stirring for 2, 4 and 8 h. Gupta et al [56] also used sulphur as a cross-linker in the fabrication of new experimental bitumen using bitumen (70/100) and high-binyl content styrene-butadiene copolymer.…”
Section: Sulphurmentioning
confidence: 99%
“…Therefore, finding a more convenient and easily promotable RAP analysis method is a prerequisite for developing HIR technique. Secondly, limitations like RAP temperature and mechanical equipment restrict the mixture temperature from rising too high during the HIRAM compaction process, thereby preserving the compaction's effectiveness [22,31,32]. It is found that the compaction effectiveness of HIR is a crucial factor influencing the occurrence of early pavement diseases [33].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Ma et al, laboratory mixing and sieving tests were performed to assess the gradation changes of fieldproduced hot recycled asphalt mixtures under different conditions [37][38][39]. The findings revealed that the fine particles within the RAP aggregates were not adequately separated from the original aggregates, resulting in decreased mixture density and increased void content [40][41][42]. Other relevant studies have demonstrated that the role of mineral particles and asphalt in RAP differs from that in conventional mixtures, leading to deviations in the expected gradation and compromising pavement compaction quality [43,44].…”
Section: Introductionmentioning
confidence: 99%